(untitled) (Edad Media. Revista de Historia, 2026)
The article analyses the importance of women in the household of Queen Maria, wife of Manuel I of Portugal, through the two wills granted by the sovereign during her lifetime. After providing a biographical sketch of the monarch and describing the essential characteristics of the wills, the article examines Maria’s relationships with her servants, as well as the rewards she established for them in her wills, offering some comparative elements with the men in her service. Particular attention is paid to the central role of figures such as Elvira de Mendoza and Aldonza Suárez, who were responsible for the organization of the sovereign’s private life and daily affairs. This study shows how women occupied key positions in the queen’s private and emotional sphere, developing forms of informal power. It also highlights the development of female court patronage, which played an essential role in shaping power and protection within the Portuguese court.